Analisis Kalimat Efektif Teks Opini Bertema Sosial dalam Website “Harian Jogja” Edisi Januari 2025 sebagai Bahan Ajar Membaca Pemahaman - Silvia Eka Hariyanti; Fijri Astami Febrianti; Ida Milantika; Alexa Ayu Qurrotul Aini; Iqlima Atqiya’ul Aulia; Asep Purwo Yudi Utomo; Ferani Mulianingsih; Iwan Hardi Saputro (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines syntax, a branch of linguistics that investigating the structure and rules for constructing larger components such as words, phrases, clauses, and sentences. The focus of this article is on analyzing sentences found in opinion texts. The primary goal is to evaluate the effectiveness of sentences in opinion articles from the January 2025 edition of